Beastly beauty - Donnelly, Jennifer (Scholastic Press, 2024)
When handsome thief Beau enters the castle that appeared out of nowhere he finds himself trapped in Arabella's curse, which can only be broken if she finds a boy who loves her for her true self--a seeming impossibility for a girl who has been told she is impossible to love.